An applied study on women's poverty in Turkey in the context of the capability approach. Issue 12 (19th October 2020) - Kurt Topuz, Senem; Erkanlı, Hülya
Abstract : Purpose: The purpose of this study is to present a detailed picture of the poverty conditions of women in Turkey in the context of the capability approach. In other words, it is to analyze their perception of how much women in Turkey can benefit from economic opportunities, political freedoms and social opportunities and to what degree they can have protective security services and transparency assurance. Design/methodology/approach: The field study was conducted in seven cities across Turkey with 741 women. Data from the field study were gathered by using the survey method. A 5-point Likert scale that was developed by the researchers and comprised of 39 statements. Findings: According to the scale means of the instrumental freedoms obtained from the survey study, it cannot be claimed that women in Turkey have a completely negative perception of all of the instrumental freedoms. However, if the instrumental freedoms are compared to each other, it is seen that the participants have different perceptions of these instrumental freedoms. Originality/value: This study basically discusses the issues of women's poverty and freedom in Turkey. In this context, the capability approach by Amartya Sen and capability deprivation; in other words, "being deprived of capabilities", that is prominent in this approach form the basis of the study. The issue of women's poverty in Turkey is dealt with through deprivations in this study in contrast to the poverty conceptualizations through the individuals' income or expenditure levels.